Exploring Inter-Generational Respect in the Context of Islamic Law Implementation: Elderly Concerns and Youth Behavior in Acehnese Coffee Shops - Fithriyah, Fithriyah; Maskur, Maskur (Intelektualita, 2024)
This study examines how inter-generational respect and value negotiation unfold in Acehnese coffee shops, where Islamic traditions meet modern influences. Through surveys with 200 young and 15 older participants, alongside interviews and observations, the research highlights how younger generations respect Islamic values but often adapt them to fit modern social settings. Behaviors like casual dress and informal language sometimes create tension with elders, who see these actions as challenges to communal and religious norms. The study introduces the Theory of Generational Value Negotiation in Public Spaces (GVNPS), framing coffee shops as spaces where self-expression and cultural traditions are continuously negotiated. Elders act as cultural guardians, while youth navigate these expectations to assert their autonomy. This framework sheds light on how generational values are shaped in public spaces. The findings, though focused on Aceh, invite exploration of similar dynamics in other cultural contexts, considering factors like globalization and varying interpretations of tradition and religion.